Ipoetry : Creating space for new literacies in the english curriculum. - Curwood, Jen Scott; Cowell, Lora Lee (Journal of Adolescent & Adult Literacy, 2011)
Within the iPoetry project, the authors introduced new literacies into the secondary English curriculum to enhance students’ critical engagement, increase their awareness of audience, and encourage their innovative use of multiple modalities. This article presents their results.
Keywords: enseignement; literacy; multimodalité